Can Children Have Ordinary Expectable Caregiving Environments in Unconventional Contexts? Quality of Care Organization in Three Mexican Same-Sex Planned Families - Salinas-Quiroz, Fernando; Rodríguez-Sánchez, Fabiola; Costa, Pedro A.; Rosales, Mariana; Silva, Paola; Cambón, Verónica (Frontiers in Psychology, 2018)
The aim of this research was to explore the elements that configure the quality of care among three Mexican same-sex planned families: two female-parented families (through donor insemination) and a male-parented one (through adoption). The first family consisted of two mothers and a 3-year-old daughter; the second one had two mothers and a 1.5-year-old set of boy twins and the third family consisted of two fathers and a 2-year-old girl. It was assumed that Ainsworth’s notions of quality of care organization are useful in order to understand caregiver-child attachment relationships, regardless of the parents’ sexual orientation. A collective case study was selected due to the fact that these families shared their “unconventionality” (i.e. parents were not heterosexual) and the fact that they were planned, but each one constituted a particular case with a unique configuration. Four trained independent observers used the q-sort methodology (Maternal Behavior Q-Sort and Attachment Q-Sort) to describe parents’ and children’s behavior, respectively. The findings showed that parents were highly sensitive and all children used them as a secure base. To provide an in-depth examination of which elements configure the quality of care, a semi-structured interview with each parent was carried out. Through a thematic analysis, an over-arching theme named Affections and Emotions was identified, together with six subthemes: 1) Creating an affective environment; 2) Being available; 3) Acknowledging and expressing emotions; 4) Perceiving, interpreting and responding adequately to the child’s real self; 5) Taking the child’s perspective into account; and 6) Agreeing on roles and dividing the tasks. In order to showcase the particular configuration of gay parenting, the male-headed family narrative is reported in detail, because gay parents have been perceived as violating traditional gender roles as well as the hegemonic model of masculinity. The findings were consistent with the notion of quality of care as proposed by Ainsworth and her collaborators. The implications of the methodological device and research regarding same-sex planned families are discussed so as to understand the organization of the caregiving environment.